A Heuristic Constructive Algorithm for Capacitor Placement on Distribution Systems - da Silva, I.C.; Carneiro, S.; de Oliveira, E.J.; de Souza Costa, J.; Rezende Pereira, J.L.; Garcia, P.A.N. (IEEE transactions on power systems, 2008)
This paper presents a heuristic constructive algorithm (HCA) for optimal capacitor placement on distribution systems. This is a nonlinear mixed integer optimization problem. In the proposed approach, the integer variables are represented using sigmoid function, thus interior point optimal power flow formulation can be applied to obtain sensitivity indexes based on Lagrange multipliers, reactive power, and bus voltage. The methodology is applied to two power distribution systems, and the results are compared with those obtained using a genetic algorithm approach.